The Effect of Local and Interarea Oscillations of Wind Turbine Generators Based on Permanent Magnet Synchronous Generators Connected to a Power System - Haydaroğlu, Cem; Yıldırım, Burak; Kılıç, Heybet; Özdemir, Mahmut Temel (My University, 2025)
In this study, the effects of wind turbine generators (WTGs) based on permanent magnet synchronous generators (PMSGs) on oscillations of the power system are investigated. The analysis studies were performed for three different cases (base case, WTG based on PMSG displacement with a suitable synchronous generator, and WTG based on PMSG connection to a suitable bus without changing the synchronous generators) in Kundur’s two-area power system and the IEEE 30-bus test system. It has been concluded that WTG based on PMSG can have positive and negative effects on power system oscillatory stability depending on the value of synchronous generator power replaced by WTG based on PMSG power and the location of WTG based on PMSG.
Keywords: Eigenvalue and sensitivity analysis; local and interarea oscillation; offshore wind turbine generator (WTG); permanent magnet synchronous generators (PMSG)